Research on the impact of Covid 19 on the Banking and Finance Sector: A Scientometric analysis (International Journal of Food and Nutritional Sciences, 2022)
The COVID-19 pandemic affected worldwide on our survival and revolutionized our lifestyle, subsequently affecting the research areas in banking and finance. Since academicians and institutions are engaged in finding the solution and future after COVID-19 in the banking sector. This study is focused on COVID-19 and banking research for this study data is collected from the Web of Science (WoS) core collection database for the period of 2020 and 2021. During the stipulated period 14400 validated documents were identified for this study and 43% of documents from 2020 and 57% of documents from 2021 were published, which shows increasing order in the publication of documents. This study found that the USA, China, and the United Kingdom are highly cited and publishing countries. Single Country publications (SCP) are more as compared to multi-country publications (MCP). In author analysis Gupta R is the most productive author succeeded by Vo XV and Lee CC are the top three authors. In journal analysis, the top three journals based on h-index are Energy Economics, Finance Research Letters, and World Development. This study found that the top 10, most cited articles with their bibliographic details are enlisted and author keyword analysis COVID-19 is the mostly used keyword by the authors.